A sociobiodiversidade como estratégia para o desenvolvimento sustentável no Sudeste do Pará, Brasil - Bernardo Tomchinsky; Felipe Fernando da Silva Siqueira; Jeronimo da Silva e Silva (Confins)
Southeast Pará is part of a complex ethnic and environmental territory in the Eastern Amazon, with a long process of occupation by indigenous peoples, accompanied by migrants and other traditional peoples and communities. From this human-ecological process, it is discussed that socio-biodiversity, as a reflection of the interaction between these populations and the environment, is an alternative for sustainable development in the region, reconciling environmental conservation, income generation and respect for local culture. There are important initiatives and laws to support this discussion, despite the practical limitations that exist, and the situations in the region that threaten the environment and traditional peoples and communities. Finally, we consider the importance of the participation of traditional peoples and communities in defining public policies that will impact their lives and territories is discussed.